Recovery from COVID-19 crisis in public health perspective - Cianciara, Dorota; Szmigiel , Andrzej; Pruszyński , Jacek (Journal of Education, Health and Sport, 2022)
Introduction. Assessments of the response to the COVID-19 pandemic so far are negative. They can be summarized as: the world was not prepared, action was insufficient, public and private institutions failed people to protect their health and everyday life. The pandemic highlighted public health weakness. Purpose. The aim is: (1) to polemic with the comparison of the pandemic to the black swan, (2) to list the negative and positive effects of the pandemic mentioned in the literature, (3) to discuss public health attributes related to counteracting epidemics, and (4) to present ways of recovery after pandemic crisis from a public health perspective. The state of knowledge. Comparing the COVID-19 pandemic to the black swan is incorrect. The literature describes the negative effects of a pandemic better than its positive effects, but there is a trend to explore unexpected positive effects or the balance of losses and gains. The public health tasks in counteracting epidemics include the development and implementation of preparedness and response plans, pursuit of health equity and fairness and care on the most vulnerable through interdisciplinary and cross-sectoral activities. The literature recommends many solutions to improve the health systems, including public health, and to strengthen the role of public health. They can be assigned to three groups: macro factors related to the political-economic context, meso factors related to the internal principles of the health system functioning and micro factors related to the functioning of the system in relations with users. Conclusions. Public health is essential to national security. It is up to decision makers, the establishment, citizens and the community to implement the postulates to improve the health and public health system.